The The Students' Speaking Attitudes toward International Islamic Conferences: A Qualitative Exploration of Confidence and Expression - Resyadi, Herman; Syam, Ferawaty; Irmayani, Irmayani; Sundari, Deny (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study investigates students' experiences and challenges when presenting at international Islamic conferences, focusing on their confidence and self-expression. Using a qualitative case study design, two participants were selected through purposive sampling, and data were collected through semi-structured interviews. The results revealed that while students expressed enthusiasm for participating in these events, they faced several challenges, including time constraints, language barriers, and adapting to the expectations of diverse audiences. Confidence levels varied; some students felt reasonably confident, while others demonstrated higher self-assurance due to thorough preparation. The findings emphasize the importance of preparation, language proficiency, and cultural sensitivity when presenting at international academic forums, especially in Islamic forums. The study also highlights the need for academic institutions to provide better support to help students develop these critical skills. Future research could explore a broader range of participants and contexts and the long-term development of public speaking confidence in such settings.